PENERAPAN MANAJEMEN RISIKO HUKUM DALAM AKTIVITAS PERBANKAN - T. Endang Ratnawati (Perspektif, 2006)
Risk is cost of loss that is caused either force majeure or overmacht. Control of law risk in a bank can be fraced foon the causal factors and the offort to control it, therefore the law risk can be minimalized.